2013
DOI: 10.1080/10807039.2012.746143
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of High Tolerance to Ecologically Relevant Lead Shot Pellet Exposures by an Upland Bird

Abstract: Upland birds that display grit ingestion behavior are potentially at risk of detrimental effects and death from lead poisoning at trap and skeet ranges and other areas where vast quantities of spent lead shot pellets abound. Because commonly cited force-feeding pellet exposure studies deviate from true field conditions, their results may not reflect true risks faced by upland birds. In particular, studies that use new shot pellets and administer more pellets than would be reasonably ingested, critically interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This range was evaluated because one laboratory study demonstrated no net effect on number of normal bobwhite quail chicks ( Colinus virginianus ) hatched per hen from ingestion of 15 to 100 lead shot by the hen (i.e., it showed reduced hatchability but increased egg production [ 13 ]), and another demonstrated 20% reduction in hatching of eggs laid by mourning dove hens that ingested 1 lead shot (but with no effect on egg production [ 11 ]). These laboratory results are for individual birds and do not account for the proportion of hens in a population ingesting lead shot within the months prior to laying eggs (often greater than a month is needed for complete excretion of lead from bobwhite quail [ 30 ]). It also does not account for the lower availability of shot in spring after burial of the lead shot by cultivation [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…This range was evaluated because one laboratory study demonstrated no net effect on number of normal bobwhite quail chicks ( Colinus virginianus ) hatched per hen from ingestion of 15 to 100 lead shot by the hen (i.e., it showed reduced hatchability but increased egg production [ 13 ]), and another demonstrated 20% reduction in hatching of eggs laid by mourning dove hens that ingested 1 lead shot (but with no effect on egg production [ 11 ]). These laboratory results are for individual birds and do not account for the proportion of hens in a population ingesting lead shot within the months prior to laying eggs (often greater than a month is needed for complete excretion of lead from bobwhite quail [ 30 ]). It also does not account for the lower availability of shot in spring after burial of the lead shot by cultivation [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using transmission electron microscopy, Pineau et al (2017) found marked subcellular toxicity in the liver associated with the ingestion of a single lead shot (0.177 ± 0.03 g) in experimentally dosed mallards ( n = 21) compared with controls ( n = 10). Experimental studies involving the dosing of pheasants (Gasparik et al 2012; Runia and Solem 2017) and northern bobwhites ( Colinus virginianus ) (Tannenbaum 2012) with lead gunshot suggest that these species appear less susceptible to the acute effects of lead poisoning than others, such as mourning doves ( Zenaida macroura ), chukars or waterfowl. While tissue (blood and/or liver) lead concentrations of pheasants and northern bobwhites increased, and some of the biological parameters measured were negatively affected (two studies), this was to a lesser degree than in other species.…”
Section: Impacts Of Lead Poisoning On Wildlifementioning
confidence: 99%
“…To be able to evaluate subclinical reproductive effects, our models assume that not all subclinical exposure results in death [34][35][36], and that the midpoint of the bounded range (range shown in Figs 1 and 2) best represents the proportion that ultimately die from lead ammunition ingestion, which includes birds dying from either direct or indirect effects. Additionally, if a study identified that ammunition was not the source of elevated lead in some carcasses, those carcasses were not included in the estimates.…”
Section: Plos Onementioning
confidence: 99%